1957
DOI: 10.1002/jmor.1051000204
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nuclei of differentiating endoderm cells as revealed by nuclear transplantation

Abstract: In an effort to determine whether cell differentiation involves genetic changes in nuclei, we have carried out a series of experiments in which nuclei from various parts of frog embryos have been transferred to enucleated eggs. The earlier work along this line showed that living nuclei of undifferentiated blastula and early gastrula cells could be successfully transplanted (Briggs and King, '52, '53). The recipient eggs developed into normal embryos, showing that there had been no change in the properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

1958
1958
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(45 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…Our data show that many factors may contribute to altered gene expression including faulty reprogramming after NT and epigenetic errors inherited from the specific type of donor nucleus. These results are consistent with NT experiments in amphibians, in which the differentiation status of the donor cell has been shown to affect the developmental potential of cloned animals (30)(31)(32)(33)(34). The data presented here indicate that highly variable gene expression, observed previously for a limited number of genes in both amphibian (34) and mammalian clones (14,15,35), affects much of the genome and further emphasizes that many changes are tolerated during cellular differentiation and even in surviving clones.…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that many factors may contribute to altered gene expression including faulty reprogramming after NT and epigenetic errors inherited from the specific type of donor nucleus. These results are consistent with NT experiments in amphibians, in which the differentiation status of the donor cell has been shown to affect the developmental potential of cloned animals (30)(31)(32)(33)(34). The data presented here indicate that highly variable gene expression, observed previously for a limited number of genes in both amphibian (34) and mammalian clones (14,15,35), affects much of the genome and further emphasizes that many changes are tolerated during cellular differentiation and even in surviving clones.…”
Section: Discussionsupporting
confidence: 91%
“…Using nuclei from frog blastomeres, Briggs and King demonstrated that the nuclei could be reprogrammed to a zygotic state and could generate early cleavage embryos when transplanted into enucleated oocytes (Briggs and King, 1952). Later, they used frog cells from several stages of embryonic develop-ment as donors to determine whether these cells still retain the same developmental potential as the zygote (Briggs and King, 1957). Of interest, they observed a gradual decline in cloning efficiency with increased donor cell differentiation.…”
Section: Mammalian Nuclear Transfer: Selected Highlightsmentioning
confidence: 99%
“…Their study covered a developmental period much later than that concerned in the present experiment however. Of particular interest are the observations of Briggs and King, of a loss of totipotency of the nuclei during gastrulation in the frog embryo (6). The regulation or reflection of developmental potency by the nuclear histones remains an enticing possibility.…”
Section: Figure 1~mentioning
confidence: 99%